Creep/recovery and stress-relaxation tests applied in a standardized carbon fiber/epoxy composite: Design of experiment approach - Monticeli, Francisco Maciel [UNESP]; Ornaghi, Heitor Luiz [UNESP]; Neves, Roberta Motta; Odila Hilário Cioffi, Maria [UNESP] (SAGE Publications, 2020)
Carbon fiber–reinforced plastic is a trend in the composite field since it has outstanding mechanical properties, which can be applied in several areas. For this work, carbon fiber–reinforced plastic composite using epoxy as matrix was molded by vacuum-assisted resin transfer molding to measure the individual influence of temperature and strain/stress on initial strain, permanent deformation, and modulus decay behavior of carbon fiber–reinforced plastic quantitatively. To achieve this purpose, void content, creep/recovery, and stress-relaxation properties were statistically evaluated by design of experiment approach–Taguchi method and analysis of variance. Results showed that both permanent deformation and modulus decay had influence on temperature and design of experiment confirmed that temperature is the main contributor to each response, considering all three viscoelastic regions (glassy, glass transition, and rubbery) and stress/strain.
Keywords: Carbon fiber–reinforced plastic; creep; design of experiments; stress relaxation; Taguchi method